The palaeoenvironment of Cervalces latifrons (Johnson, 1874) from Fornaci di Ranica (late Early Pleistocene, Northern Italy) - BREDA, Marzia; PINI R.; RAVAZZI C. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2005)
We compared the pollen content and infrared (IR) spectra of clay extracted from the fossil braincase of a broad-fronted moose [Cervalces latifrons (Johnson, 1874)] from Fornaci di Ranica (late Early Pleistocene, northern Italy) with the complete pollen and IR record from the sequence of palustrine–lacustrine sediments at the site. This allowed us to correlate the remains with a specific pollen zone, characterized by forest retreat and expansion of herbaceous communities. At the time of Cervalces occurrence around the basin of Fornaci di Ranica, the regional vegetation consisted in scattered conifer forests with Pinus sylvestris/mugo and dry meadows and/or steppes. Around the basin and along watercourses, the vegetation probably consisted of moist meadows with forb stands, palustrine herb associations and shallow water communities with telmatic helophytes. A morpho-functional comparison between living Alces alces and its extinct relative Cervalces latifrons was carried out, suggesting adaptation to similar marshy habitats, with bushes and strewn debris and similar diet. Palaeobotanical and palaeontological data from other European sites bearing remains of Cervalces and Alces indicate that these animals could have lived either in boreal forests and in mixed conifer/deciduous forests and in meadow steppes. Warm temperate deciduous forests seem to be excluded.